The Effectiveness of Trauma-Aware Parenting Intervention on Relationship between Attachment and Emotional Disturbance in Adoptive Families - Mehrana Mehrana; Mansoureh Bahramipour Isfahani (پژوهش‌های علوم شناختی و رفتاری)
The study was conducted with the aim of investigating the effectiveness of trauma–-informed parenting on the relationship between attachment and emotional disturbance in adoptive families. The research method was semi-experimental and included experimental and control groups with pre-test, post-test, and a 45-day follow-up period. The statistical population included all adoptive families from care centers for orphaned and abused children in the city of Isfahan in the summer, which were selected by the available sampling method among those who were referred to the care centers for orphaned and abused children in the city of Isfahan. Twenty people (20 experimental people) and (20 control people) were randomly divided to two groups. The research tools include Halpern and Kapenerek's relationship between the attachment questionnaire, and Simmons and Gaher's emotional disturbance. Trauma-informed parenting training was conducted in 120-minute sessions. Data analysis was done using statistical methods and SPSS 23 software.  The findings showed that the trauma- informed parenting intervention is effective in the relationship between attachment, and emotional turmoil in adoptive families (p <0.01). Therefore, it can be concluded that the intervention of conscious parenting is suitable for reducing the problems caused by adoption.IntroductionFamily is the most important determining factor of children's behavior and plays a very important role in explaining their social position. Children learn the right and wrong of something in the family, and the family plays a significant role in the formation of their behavior. On the other hand, in our country every year more than 2000 children are admitted to care systems (boarding institutions and nurseries) due to parental neglect, violence or misbehavior, the death or divorce of parents (Annual report of welfare organization activity, 2017). Adoption is a complex social process that is often challenging and not always satisfactory. Adoptive parents may not have the knowledge  and skills necessary to meet the needs of the adopted child (Fisher, 2015). Children's adjustment issues and lack of parenting skills in adoptive families can lead to the failure or dissolution of adoption (Steinberg, Stacey, 2023). One of these methods is conscious parenting (CP) . Conscious parenting means awareness in all your interactions with your child (Shiraninia, et al, 2019). The goal of conscious parenting is to connect more deeply with children and nurture their nature. This model includes five dimensions of listening with full attention, non-judgmental acceptance of oneself and the child, emotional awareness towards oneself and the child, and self-regulation in relation to parenting (Matin et al, 2021). Various variables are very important in the relationship between adoptive families and children under their care, and one of these factors is attachment style. Bowlby (1969) identified three secure attachment styles, avoidant insecure attachment and ambivalent insecure attachment. It  is possible to acknowledge the child's expectations about the sensitivity, availability and responsiveness of the primary caregiver, leading to the formation of differences in the type of infant's attachment depends on the caregiver. Through these factors, the child gradually internalizes models of himself and others, which are called internal active models in the attachment perspective (Mohan, 2023). Emotional disturbance is also another influencing factor among adoptive families, in fact, emotional disturbance is a complex process and a combination of several main emotions such as anxiety, stress, depression and despair, and it usually occurs when a person is under stressful conditions, but he/she is unable to manage it (Ringeisen et al 2017). Emotional disturbance has 4 physical, emotional, cognitive and behavioral components (Inzlicht et al, 2015). Generally, it can be said that the importance of parenting, attachment styles (Quintigliano et al 2021) , and the effects of emotional disturbance (Hou et al 2020) are some factors that affect adoptive families, especially adoptive children. Considering the importance of the topic in improving parenting skills in adoptive families, different training interventions have been proposed, one of which is the conscious parenting model. This study seeks to answer the following question: Does trauma–-informed parenting affect on attachment style and emotional turmoil in adoptive families effective?​MethodsThe research method was semi-experimental with a pre-test, and post-test design and a 45-day follow-up period with a heterogeneous control group. This research had the ethics code number IR. IAU. KHUISF. REC.1402.338. ResultsBased on the descriptive findings, the average attachment scores in the experimental group increased more than the control in the post-test and follow-up stages compared to the pre-test. The average emotional disturbance scores in the experimental group compared to the control showed a greater decrease in the post-test and follow-up phase than in the pre-test. Analysis of variance with repeated measures was used to investigate the research hypotheses, which allows the researcher to compare the experimental group (trauma–-informed parenting) and the control group in the research variables. Table 1: Descriptive indices of the scores of the research variables by two groups and three stages of the research ExperimentControlpre-testpost-testFollow-uppre-testpost-testFollow-upAttachment stylemean45.266.5566.3546.3546.146SD16/6710/9812/9716/1315/8615/69Emotional disturbancemean46/1536/0536/1546/8546/746/65SD11/4310/88/611/2611/0211/003 Table 2: The result of Tests of between-subject and within-Subjects in variables VariableeffectsourceSSdfMSFpeffect sizepowerEmotional turmoilBetween subjectsgroup15.40891115.408917.170.0110.1590.742within the subjecttime697.0171.003695.24811.4970.0020.2320.911Time × group650.2171.003648.56710.720.0020.2200.891Positive adaptive evolutionBetween subjectsgroup320.3111320.3116.840.0130.1530.722within the subjecttime176.1171.37128.12715.350.0010.2280.991Time × group218.6171.37159.04619.0570.0010.3340.998Emotional reactionBetween subjectsgroup414.4081414.40839.630.0010.511.000within the subjecttime96.5171.51863.3613.0580.0010.2560.985Time × group98.6171.51864.94413.340.0010.260.988Negative behaviorsBetween subjectsgroup310.4081310.40817.0890.0010.3100.981within the subjecttime228.3171.54148.07870.5370.0010.6501.000Time × group204.0171.54132.32663.030.0010.6241.000Avoiding the support of the attachment figure/caregiverBetween subjectsgroup582.2081585.20836.310.0010.4891.000within the subjecttime301.6171.29232.85772.740.0010.6571.000Time × group 254.7181.29196.72661.450.0010.6181.000The results have shown the interaction of time and group membership in the variables of emotional disturbance (F = 10.72, p < 0.01), positive adaptive development (F = 19.05, p < 0.001), emotional reaction (F =13, p <0.001), negative behaviors (F =63, p  <0.001) and avoidance of caregiver support (F =61.45, p <0.001) are significant. It shows that the changes in the pre-test, post-test and follow-up stages were significant in each of the groups. The results of the Bonferroni post hoc test for comparing the experimental and control groups in the research stages are presented in Table (3). Table 3: Result of Bonferroni test for Comparison of two groups according to research variables in two stages of post-test and follow-upMeaningfulnessEffect sizeAverage differenceStageVariable0/8460/001-0/7Pre-testEmotional Disturbance0/0010/278-10/65Post-test0/0010/27610/5Follow-up0/730/003-0/55Pre-testPositive adaptive evolution0/0010/2755/1Post-test0/0010/3245/25Follow-up0/1180/063-1/2Pre-testEmotional reaction0/0010/451-4/55Post-test 0/0010/579-5/4Follow-up0/6170/0070/4Pre-testNegative behaviors0/0010/551-5/65Post-test0/0010/381-4/4Follow-up    Avoiding face SupportAttachment/caregiver0/7250/003-0/3Pre-test0/0010/634-/565Post-test0/0010/621-6/3Follow-up The results in Table (3) show that the difference between the experimental group, i.e., trauma-aware parenting, and the control group in all research variables in the pre-test stage is insignificant (p<0.05); however, the results show that the difference between the two groups in the variables of emotional disturbance and the dimensions of relationships between attachment in the post-test and follow-up stages is significant (p<0.001). The effect of trauma-aware parenting on emotional disturbance is 27.8% and 27.6% in the follow-up stage. The effect of training on the dimensions of positive adaptive development, emotional reaction, negative behaviors and avoidance of caregiver support is 27.5%, 45%, 55% and 63.6% in the post-test and 32.4%, 57.9%, 38% and 62% in the follow-up stage, respectively.Also, the results of the paired Bonferroni test showed that in the variable of parent-child attachment style, there was no significant difference between the experimental and control groups in the pre-test stage (p<0.05). However, the difference in the mean scores of this variable in the experimental and control groups was significant in the post-test and follow-up stage (p<0.001). The effect of the harm-aware parenting intervention on parent-child attachment style in the post-test stage was 39.8% and 40% in the follow-up stage. In the variable of emotional disturbance, there was no significant difference between the experimental and control groups in the pre-test stage (p<0.05). However, the difference in the mean scores of this variable in the experimental and control groups was significant in the post-test and follow-up stage (p<0.001). The effect of the harm-aware parenting intervention in the post-test stage was 27.8% and 27.6% in the follow-up stage. DiscussionsInformed parents value both autonomous behavior and discipline, and rational control and calculated freedom make children internalize the rules and principles of correct behavior and feel responsible for their actions and behavior. In addition to being warm and affectionate, these parents push their children towards independence, thus providing an environment for the child to feel valued. These mentioned characteristics are also the characteristics of people with a secure attachment style who, in their internal activation patterns and others, reach the cognitive conclusion that they are valuable and worth being cared for, and that others (here, adoptive parents) are caring and responsive people. They will be present when needed and will satisfy their needs. People with secure attachment are those people who have a positive sense of themselves and a positive understanding of others, and are more socially confident and successful. Therefore, the intervention of conscious parenting by strengthening parents' awareness and knowledge in the seventh steps by practicing compassion and kindness and re-connecting with their body in the position of a parent, watching the body during the stress of parenting, was able to make them aware of the benefits of a secure attachment style. Therefore, it is not far from the expectation that conscious parenting by strengthening such steps and exercises will provide a safe environment with a safe attachment style. Conscious parenting acts as a potential psychological resource in times of stress and helps parents to cope more adaptively and avoid the destructive effects of psychological evaluations related to parenting and family (Turpyn & Chaplin, 2016). Also, in this method, parents learn to be kind and compassionate towards themselves, their children and others by doing love and friendship meditation and self-compassion exercises, and this reduces self-blame and stress in them. Also, experiencing children with the five senses, such as touch and hugging, increases the release of oxytoxin and, as a result, reduces stress (Hou et al., 2020) , and beyond that, with the reduction of stress, the emotional turmoil that governs relationships in children is also reduced. This training is suitable for parents who themselves suffer from psychological problems (Dalen et al, 2020) and can decrease their children's psychological problems and emotional turmoil through increasing their awareness.  The study was conducted with the aim of investigating the effectiveness of trauma–-informed parenting on the relationship between attachment and emotional disturbance in adoptive families. The research method was semi-experimental and included experimental and control groups with pre-test, post-test, and a 45-day follow-up period. The statistical population included all adoptive families from care centers for orphaned and abused children in the city of Isfahan in the summer, which were selected by the available sampling method among those who were referred to the care centers for orphaned and abused children in the city of Isfahan. Twenty people (20 experimental people) and (20 control people) were randomly divided to two groups. The research tools include Halpern and Kapenerek's relationship between the attachment questionnaire, and Simmons and Gaher's emotional disturbance. Trauma-informed parenting training was conducted in 120-minute sessions. Data analysis was done using statistical methods and SPSS 23 software.  The findings showed that the trauma- informed parenting intervention is effective in the relationship between attachment, and emotional turmoil in adoptive families (p <0.01). Therefore, it can be concluded that the intervention of conscious parenting is suitable for reducing the problems caused by adoption. Keywords: Emotional Disturbance, Adoptive Families, Relationship Between Attachment, Trauma-Aware Parenting Intervention. IntroductionFamily is the most important determining factor of children's behavior and plays a very important role in explaining their social position. Children learn the right and wrong of something in the family, and the family plays a significant role in the formation of their behavior. On the other hand, in our country every year more than 2000 children are admitted to care systems (boarding institutions and nurseries) due to parental neglect, violence or misbehavior, the death or divorce of parents (Annual report of welfare organization activity, 2017). Adoption is a complex social process that is often challenging and not always satisfactory. Adoptive parents may not have the knowledge  and skills necessary to meet the needs of the adopted child (Fisher, 2015). Children's adjustment issues and lack of parenting skills in adoptive families can lead to the failure or dissolution of adoption (Steinberg, Stacey, 2023). One of these methods is conscious parenting (CP) . Conscious parenting means awareness in all your interactions with your child (Shiraninia, et al, 2019). The goal of conscious parenting is to connect more deeply with children and nurture their nature. This model includes five dimensions of listening with full attention, non-judgmental acceptance of oneself and the child, emotional awareness towards oneself and the child, and self-regulation in relation to parenting (Matin et al, 2021). Various variables are very important in the relationship between adoptive families and children under their care, and one of these factors is attachment style. Bowlby (1969) identified three secure attachment styles, avoidant insecure attachment and ambivalent insecure attachment. It  is possible to acknowledge the child's expectations about the sensitivity, availability and responsiveness of the primary caregiver, leading to the formation of differences in the type of infant's attachment depends on the caregiver. Through these factors, the child gradually internalizes models of himself and others, which are called internal active models in the attachment perspective (Mohan, 2023). Emotional disturbance is also another influencing factor among adoptive families, in fact, emotional disturbance is a complex process and a combination of several main emotions such as anxiety, stress, depression and despair, and it usually occurs when a person is under stressful conditions, but he/she is unable to manage it (Ringeisen et al 2017). Emotional disturbance has 4 physical, emotional, cognitive and behavioral components (Inzlicht et al, 2015). Generally, it can be said that the importance of parenting, attachment styles (Quintigliano et al 2021) , and the effects of emotional disturbance (Hou et al 2020) are some factors that affect adoptive families, especially adoptive children. Considering the importance of the topic in improving parenting skills in adoptive families, different training interventions have been proposed, one of which is the conscious parenting model. This study seeks to answer the following question: Does trauma–-informed parenting affect on attachment style and emotional turmoil in adoptive families effective?​MethodsThe research method was semi-experimental with a pre-test, and post-test design and a 45-day follow-up period with a heterogeneous control group. This research had the ethics code number IR. IAU. KHUISF. REC.1402.338. ResultsBased on the descriptive findings, the average attachment scores in the experimental group increased more than the control in the post-test and follow-up stages compared to the pre-test. The average emotional disturbance scores in the experimental group compared to the control showed a greater decrease in the post-test and follow-up phase than in the pre-test. Analysis of variance with repeated measures was used to investigate the research hypotheses, which allows the researcher to compare the experimental group (trauma–-informed parenting) and the control group in the research variables. Table 1: Descriptive indices of the scores of the research variables by two groups and three stages of the research ExperimentControlpre-testpost-testFollow-uppre-testpost-testFollow-upAttachment stylemean45.266.5566.3546.3546.146SD16/6710/9812/9716/1315/8615/69Emotional disturbancemean46/1536/0536/1546/8546/746/65SD11/4310/88/611/2611/0211/003 Table 2: The result of Tests of between-subject and within-Subjects in variables VariableeffectsourceSSdfMSFpeffect sizepowerEmotional turmoilBetween subjectsgroup15.40891115.408917.170.0110.1590.742within the subjecttime697.0171.003695.24811.4970.0020.2320.911Time × group650.2171.003648.56710.720.0020.2200.891Positive adaptive evolutionBetween subjectsgroup320.3111320.3116.840.0130.1530.722within the subjecttime176.1171.37128.12715.350.0010.2280.991Time × group218.6171.37159.04619.0570.0010.3340.998Emotional reactionBetween subjectsgroup414.4081414.40839.630.0010.511.000within the subjecttime96.5171.51863.3613.0580.0010.2560.985Time × group98.6171.51864.94413.340.0010.260.988Negative behaviorsBetween subjectsgroup310.4081310.40817.0890.0010.3100.981within the subjecttime228.3171.54148.07870.5370.0010.6501.000Time × group204.0171.54132.32663.030.0010.6241.000Avoiding the support of the attachment figure/caregiverBetween subjectsgroup582.2081585.20836.310.0010.4891.000within the subjecttime301.6171.29232.85772.740.0010.6571.000Time × group 254.7181.29196.72661.450.0010.6181.000The results have shown the interaction of time and group membership in the variables of emotional disturbance (F = 10.72, p < 0.01), positive adaptive development (F = 19.05, p < 0.001), emotional reaction (F =13, p <0.001), negative behaviors (F =63, p  <0.001) and avoidance of caregiver support (F =61.45, p <0.001) are significant. It shows that the changes in the pre-test, post-test and follow-up stages were significant in each of the groups. The results of the Bonferroni post hoc test for comparing the experimental and control groups in the research stages are presented in Table (3). Table 3: Result of Bonferroni test for Comparison of two groups according to research variables in two stages of post-test and follow-upMeaningfulnessEffect sizeAverage differenceStageVariable0/8460/001-0/7Pre-testEmotional Disturbance0/0010/278-10/65Post-test0/0010/27610/5Follow-up0/730/003-0/55Pre-testPositive adaptive evolution0/0010/2755/1Post-test0/0010/3245/25Follow-up0/1180/063-1/2Pre-testEmotional reaction0/0010/451-4/55Post-test 0/0010/579-5/4Follow-up0/6170/0070/4Pre-testNegative behaviors0/0010/551-5/65Post-test0/0010/381-4/4Follow-up    Avoiding face SupportAttachment/caregiver0/7250/003-0/3Pre-test0/0010/634-/565Post-test0/0010/621-6/3Follow-up The results in Table (3) show that the difference between the experimental group, i.e., trauma-aware parenting, and the control group in all research variables in the pre-test stage is insignificant (p<0.05); however, the results show that the difference between the two groups in the variables of emotional disturbance and the dimensions of relationships between attachment in the post-test and follow-up stages is significant (p<0.001). The effect of trauma-aware parenting on emotional disturbance is 27.8% and 27.6% in the follow-up stage. The effect of training on the dimensions of positive adaptive development, emotional reaction, negative behaviors and avoidance of caregiver support is 27.5%, 45%, 55% and 63.6% in the post-test and 32.4%, 57.9%, 38% and 62% in the follow-up stage, respectively.Also, the results of the paired Bonferroni test showed that in the variable of parent-child attachment style, there was no significant difference between the experimental and control groups in the pre-test stage (p<0.05). However, the difference in the mean scores of this variable in the experimental and control groups was significant in the post-test and follow-up stage (p<0.001). The effect of the harm-aware parenting intervention on parent-child attachment style in the post-test stage was 39.8% and 40% in the follow-up stage. In the variable of emotional disturbance, there was no significant difference between the experimental and control groups in the pre-test stage (p<0.05). However, the difference in the mean scores of this variable in the experimental and control groups was significant in the post-test and follow-up stage (p<0.001). The effect of the harm-aware parenting intervention in the post-test stage was 27.8% and 27.6% in the follow-up stage. DiscussionsInformed parents value both autonomous behavior and discipline, and rational control and calculated freedom make children internalize the rules and principles of correct behavior and feel responsible for their actions and behavior. In addition to being warm and affectionate, these parents push their children towards independence, thus providing an environment for the child to feel valued. These mentioned characteristics are also the characteristics of people with a secure attachment style who, in their internal activation patterns and others, reach the cognitive conclusion that they are valuable and worth being cared for, and that others (here, adoptive parents) are caring and responsive people. They will be present when needed and will satisfy their needs. People with secure attachment are those people who have a positive sense of themselves and a positive understanding of others, and are more socially confident and successful. Therefore, the intervention of conscious parenting by strengthening parents' awareness and knowledge in the seventh steps by practicing compassion and kindness and re-connecting with their body in the position of a parent, watching the body during the stress of parenting, was able to make them aware of the benefits of a secure attachment style. Therefore, it is not far from the expectation that conscious parenting by strengthening such steps and exercises will provide a safe environment with a safe attachment style. Conscious parenting acts as a potential psychological resource in times of stress and helps parents to cope more adaptively and avoid the destructive effects of psychological evaluations related to parenting and family (Turpyn & Chaplin, 2016). Also, in this method, parents learn to be kind and compassionate towards themselves, their children and others by doing love and friendship meditation and self-compassion exercises, and this reduces self-blame and stress in them. Also, experiencing children with the five senses, such as touch and hugging, increases the release of oxytoxin and, as a result, reduces stress (Hou et al., 2020) , and beyond that, with the reduction of stress, the emotional turmoil that governs relationships in children is also reduced. This training is suitable for parents who themselves suffer from psychological problems (Dalen et al, 2020) and can decrease their children's psychological problems and emotional turmoil through increasing their awareness.